Contextual Learning Approach: Development of Worksheet in Physics Subjects - Wulandari, Wike Tio (Schrödinger: Journal of Physics Education, 2023)
Research Objectives: The purpose of this study was to develop worksheets using a contextual learning approach in learning physics subject to elasticity and Hooke’s law. Methodology: This research includes research and development or Research and Development, Dick and Carey (2009) the steps are (1) Analysis of learning objectives; (2) Learning analysis; (3) Analysis of students and their environment; (4) formulate specific objectives; (5) Development of assessment instruments; (6) Development of learning strategies; (7) Develop and select learning materials; (8) Formative evaluation; (9) Revision; (10) Summative evaluation, but the authors limit it to the ninth step. Main Findings: The results of this study are worksheets using the contextual learning approach to learning the physics of elasticity and Hooke’s law which have been declared feasible by the validator. Based on the results obtained, it can be concluded that worksheets using the contextual learning approach in learning elastic physics and Hooke’s law are well used as teaching materials for students in class X SMA/MA. Novelty/Originality of Research: Integrating the values of everyday life is important to be integrated into learning, therefore, teachers are required to create learning innovations, such as worksheets based on everyday life.